Swedish primary teacher education students’ perspectives on linear equations - Andrews, Paul (NOMAD Nordic Studies in Mathematics Education, 2020)
Linear equations, connecting arithmetic to the symbolism of formal mathematics, represent a key topic of mathematics. However, the understanding primary teacher education students bring to their studies has been rarely examined. In this study, students were invited to explain in writing how an unannotated solution to x + 5 = 4x – 1 had been conceptualised by the hidden solver. Data, coded against an iteratively derived framework, showed that most students were familiar with linear equations, able to articulate an objective for equation solving and offer solution strategies, typically based on either doing the same to both sides, swapping the side swapping the sign or both.